STATE BOREDOM IN ONLINE CLASSROOMS: A STUDY OF NOVICE AND EXPERIENCED IRANIAN EFL TEACHERS - Masoomeh Estaji; Seyedeh Azadeh Sadr (TEFLIN Journal)
Teachers and students frequently experience positive and negative emotions in EFL classrooms. Boredom is a negative feeling whose detrimental influence on various aspects of the learning process and achievement has been well established. However, in the EFL context, particularly among EFL teachers, this aspect remains under-examined. Using a mixed-methods research design, the current study examined 263 Iranian novice and experienced EFL teachers with online teaching experience to compare their state boredom and perceptions of its signs. For qualitative analysis, 15 novice and 15 experienced teachers were selected from the respondents to review their open-ended questionnaire answers. Additionally, 16 teachers participated in a semi-structured interview. The results of Mann-Whitney U-test revealed a significant difference in state boredom between teacher groups, with novice teachers experiencing higher level of boredom in online classrooms. Qualitative analysis using MAXQDA showed differing perceptions of boredom between novice and experienced teachers in online settings. Novice teachers primarily viewed boredom as attention failure, while experienced teachers had a deeper understanding, including loss of motivation and enthusiasm. The results suggest that targeted support and training for novice teachers in online environments are critical approaches to enhance engagement and reduce boredom, fostering a more comprehensive understanding of motivational factors.